2010
DOI: 10.1029/2010gc003051
|View full text |Cite
|
Sign up to set email alerts
|

Light elements, volatiles, and stable isotopes in basaltic melt inclusions from Grenada, Lesser Antilles: Inferences for magma genesis

Abstract: [1] Grenada Island is located at the southern end of the Lesser Antilles. Grenada lavas display a large range in compositions which includes picrites, representing the parental melt of all Grenada suites. We present here an extensive study of major, light and volatile elements combined with dD, d11 B and d 7Li determinations of melt inclusions hosted in olivines (Fo 86-91 ) from picritic scoriae. The major element compositions of melt inclusions encompass those of Grenada basalts. Their H 2 O contents typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 142 publications
(208 reference statements)
0
14
0
Order By: Relevance
“…• There are only a third as many analyses of C-series (26) as M-series 75analyses in our database, suggesting the Grenadian crust consists dominantly of M-series material. Furthermore, xenoliths we analyzed have predominately M-series isotopic compositions, and most of the melt inclusions analyzed by Bouvier et al (2010) appear to be M-series related. (It could be argued that the melt inclusions are M series only because the host lava is also, but the inclusions display considerable heterogeneity and appear largely unrelated to the host lava.)…”
Section: Assimilation or Magma Mixing?mentioning
confidence: 97%
See 2 more Smart Citations
“…• There are only a third as many analyses of C-series (26) as M-series 75analyses in our database, suggesting the Grenadian crust consists dominantly of M-series material. Furthermore, xenoliths we analyzed have predominately M-series isotopic compositions, and most of the melt inclusions analyzed by Bouvier et al (2010) appear to be M-series related. (It could be argued that the melt inclusions are M series only because the host lava is also, but the inclusions display considerable heterogeneity and appear largely unrelated to the host lava.)…”
Section: Assimilation or Magma Mixing?mentioning
confidence: 97%
“…Where the major-element compositions of samples in this range are ambiguous as to which series a sample belongs, we have used isotope ratios as additional criteria (see below). The melt inclusions analyzed by Bouvier et al (2010) plot mainly within the M-series trends and are distinct from the C series, which is not surprising since the Queen's Park scoria cone, from which these samples were taken, consists of M-series picritic basalt (our sample from this site is GDA008, the majorelement composition of which was previously reported by Devine, 1995). However, a few of the inclusions have CaO contents well above those seen in M-series lavas, and in some cases above those of the C series, at comparable MgO.…”
Section: Geochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The δD-values of melt inclusions in phenocrysts from subduction settings (Shaw et al, 2008;Bouvier et al, 2010;Métrich and Deloule, 2014) might be used to constrain the δD-value of slabderived fluids provided that the D/H fractionation factor, α fluid-melt , is known. For example Shaw et al (2008) suggested that the average δD-value of melt inclusions from the Mariana arc (−34h) reflects the δD-value of the aqueous fluids released by the subducting slab, and thus might be used to determine the extent of slab dehydration.…”
Section: Geochemical Implicationsmentioning
confidence: 99%
“…Straub et al 2004;Le Voyer et al 2008;Sadofsky et al 2008;Bouvier et al 2010;Sorbadere et al 2011). The composition of the metasomatic agent is usually calculated from mass balance assuming a mixing between the depleted mantle (DMM) and this agent, either a slab aqueous fluid or a slab melt (e.g.…”
Section: Effect Of Melt Structure On F and CL Partition Coefficientsmentioning
confidence: 99%